Effect of Leucas aspera on Lead Acetate Induced Nephrotoxicity in Rats - Soma Sekhar Reddy, K.; Padmanabha Reddy, Y.; Ravindra Reddy, J.; Ramesh, B.; Srirama Chandra, M.; Pradeep Kumar, B.; Sandhya Rani, P. (Asian Journal of Chemistry, 2010)
The present work reveals that lead acetate treated 160 mg/kg, kidney showed revealing areas of haemorrhages, atrophic glomerular tufts, tubular epithelial cells revealing degenerative changes. Methanolic extract of Leucas aspera treated 100 mg/kg kidney showed mild focal haemorrhages with almost normal appearance of the glomeruli and mild degenerative changes in the tubular epithelial cells. Standard (silymarin) treated 140 mg/kg kidney showed revealing normal glomerular architecture and very mild changes in the tubular epithelial cells. Lignans isolated from methanolic extract of Leucas aspera may be useful as nephroprotective agent.